Clozapine sensing through paper-based microfluidic sensors directly modified via electro-deposition and electro-polymerization - Ghanbari, Mohammad Hossein; Biesalski, Markus; Friedrich, Oliver; Etzold, Bastian (Sensors & Diagnostics, 2024)
Microfluidic electrochemical sensors (μCS) can be portable, highly sensitive, and low-cost but are less frequently studied nor applied. Additionally, simultaneous electro-deposition of gold nanoparticles (ED (AuNPs)) and electro-polymerization of l-cysteine (EP (l-cys)) are introduced for the first time for modifying the surface of the working electrode through a paper-based microfluidic sensor. This study depicts that by employing such modification, the electrochemically active surface area (ECSA) and the electron transfer rate are increased together and result in improved sensitivity. The modified μCS is depicted to enable sensitive voltametric determination of, e.g., clozapine (CLZ), an anti-psychotic drug to treat schizophrenia. The proposed sensor was characterized by different techniques, and several key parameters were optimized. Under the optimum conditions and using square-wave voltametry (SWV), a linear dose-response for a concentration range from 0.5 to 10.0 μM of CLZ was achieved. The limit of detection and sensitivity resulted in 70.0 nM and 0.045 mA cm−2 μM−1, respectively. Besides, this excellent sensitivity combines with high stability, which was tested for six repetitive measurements with a single device resulting in high reproducibility. Additionally, this procedure was validated with measurements of clozapine in human blood plasma, which demonstrated the excellent applicability of the device, rendering it a promising platform for point-of-care diagnostics and environmental monitoring.
CRIS-Team Scopus Importer:2024-11-08

Controlling Temporally and Spatially Homogeneous Temperature Distribution of Paper Substrates by Biogenic Phase Change Hybrid Material Coatings - Breuer, Carina; Neuenfeld, Lukas; Ghanbari, Mohammad Hossein; Etzold, Bastian; Biesalski, Markus (Advanced Materials Interfaces, 2024)
Here the performance of phase change material (PCM)-coated paper made from unbleached kraft pulp is introduced. The applied PCM consists of a mixture of ethylene glycol distearate (EGDS), a well-known PCM wax material, and a fully substituted cellulose stearoyl ester (CSE). Transfer of the PCM material onto/into paper is achieved by spray as well as blade coating of EGDS + CSE mixture. It is shown that the kind of coating method used does not interfere with observed PCM properties. The significantly higher melt viscosity of the EGDS + CSE blends ensures that the EGDS wax is not bleeding out of the paper, which avoids the use of further encapsulation processes. The PCM behavior, as observed by thermal load measurements, and the thermal buffering of the coated paper is a function of the applied mass of the PCM material applied. The thermal retention exhibited a quasi-isothermal behavior at ≈65 °C with EGDS + CSE coatings. These effects can offset fluctuations in temperature, and the PCM papers can be employed to achieve a more uniform temperature setting. PCM-modified papers are therefore interesting candidates for paper-based packaging or for use in paper-based sensors, where overheating can strongly affect reliability of results.
CRIS-Team Scopus Importer:2024-11-22
Keywords: barrier coating; cellulose ester; paper coating; phase change material; wax

Screen printed 3D microfluidic paper-based and modifier-free electroanalytical device for clozapine sensing - Ghanbari, Mohammad Hossein; Biesalski, Markus; Friedrich, Oliver; Etzold, Bastian (Analyst, 2024)
The increasing demand in healthcare for accessible and cost-effective analytical tools is driving the development of reliable platforms to the customization of therapy according to individual patient drug serum levels, e.g. of anti-psychotics in schizophrenia. A modifier-free microfluidic paper-based electroanalytical device (μPED) holds promise as a portable, sensitive, and affordable solution. While many studies focus on the working electrode catalysts, improvements by engineering aspects e.g. of the electrode arrangement are less reported. In our study, we demonstrate the enhanced capabilities of the 3D electrode layout of μPED compared to 2D μPED arrangements. We especially show that screen printing can be employed to prepare 3D μPEDs. We conducted a comparison of different 2D and 3D electrode arrangements utilizing cyclic voltammetry in [Fe(CN)6]3−/4−, along with square-wave voltammetry for clozapine (CLZ) sensing. Our findings reveal that the utilization of the 3D μPED leads to an increase in both the electrochemically active surface area and the electron transfer rate. Consequently, this enhancement contributes to improve sensitivity in the CLZ sensing. The 3D μPED clearly outperforms the 2D μPED arrangement in terms of signal strength. With the 3D μPED under the optimized conditions, a linear dose-response for a concentration range from 7.0 to 100 μM was achieved. The limit of detection and sensitivity was determined to be 1.47 μM and 1.69 μA μM−1 cm−2, respectively. This evaluation is conducted in the context of detection and determination of CLZ in a human blood serum sample. These findings underscore the potential of the 3D μPED for future applications in pharmacokinetic analyses and clinical tests to personalize the management of schizophrenia.
CRIS-Team Scopus Importer:2024-10-25

Superior performance of N-doped carbon Nanoonions/Nafion based microfluidic electrochemical Cd2+ sensor when compared to Screen-Printed Carbon-Based electrode devices - Ghanbari, Mohammad Hossein; Norouzi, Zahra; Biesalski, Markus; Etzold, Bastian (Microchemical Journal, 2024)
The sensing of cadmium is important due to its highly toxic effects on various organs of humans and animals. Commonly employed are screen-printed carbon-based electrodes (SPCE) as suitable low-cost sensing platform. Microfluidic electrochemical sensor (μCS) can also be portable, highly sensitive, and low-cost but are up to now only seldom studied and applied. Here we demonstrate the superior performance of μCS over SPCE arrangements for sensing ultra-trace of Cd2+. Additionally, N-doped carbon nanoonions (N-CNOs) are introduced as sustainable non-metallic modifier and employed for both sensing arrangements. The study depicted that employing the modifier the electrochemically active surface area and the electron transfer rate in both arrangements is improved together with improve sensitivity. Both arrangements were compared using cyclic voltammetry and electrochemical impedance spectroscopy in [Fe(CN)6]3−/4−, and also square-wave anodic stripping voltammetry (SWASV) for Cd2+ sensing. The µCS arrangement clearly outperforms the SPCE arrangement in signal strength. For the final device (μCS modified with N-CNOs) a linear concentration range from 1.0 to 100 μg L−1 was achieved. The limit of detection and sensitivity resulted to 0.25 μg L−1 and 1.02 μA µg−1 L cm−2, respectively. Besides this excellent sensitivity combines with high stability, which was tested for 8 repetitive measurements with a single device resulting in high reproducibility. Additionally, this procedure was favorably employed for measurements of Cd2+ in different real samples, which demonstrated the excellent applicability of the device for the adsorption and detection of heavy metal ions.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Cadmium; Microfluidic electrochemical sensor; N-doped carbon nanoonions; Screen-printed carbon-based electrode